Water Treatment Methods and Its Applications for Electrochemical Oxidation: Addressing Scarcity and Ensuring Water Purity through Electrochemical Oxidation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
By producing hydroxylic radicals, electrochemical oxidation offers an incredibly efficient oxidation environment that allows adequate water purification to eliminate persistent contaminants. In this study we have discussed about the scarcity in terms of quantity and quality, need for water and wastewater treatment, common water treatment methods, electrochemical oxidation, applications of electrochemical oxidation in wastewater treatment, need of water disinfection which is concluded that Water fewer flowed through the waterways will minimize piping, rehabilitation and sediment disturbances, while creating an infrastructure best maintained. This can indicate fewer drainage of the storm by collectors for infiltration. Maybe one day, with improved storage and distribution methods, water supply problems would be overturned.